2006
DOI: 10.1086/507788
|View full text |Cite
|
Sign up to set email alerts
|

The Rise Time of Type Ia Supernovae from the Supernova Legacy Survey

Abstract: We compare the rise times of nearby and distant Type Ia supernovae (SNe Ia) as a test for evolution using 73 highredshift spectroscopically confirmed SNe Ia from the first 2 years of the 5 year Supernova Legacy Survey (SNLS) and published observations of nearby SNe. Because of the ''rolling'' search nature of the SNLS, our measurement is approximately 6 times more precise than previous studies, allowing for a more sensitive test of evolution between nearby and distant SNe. Adopting a simple t 2 early-time mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
80
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 39 publications
22
80
5
Order By: Relevance
“…The slow evolution of brightness in SN 2009dc around the maximum suggests that the rising time of the bolometric luminosity is comparable to or slightly longer than those of SN 2006gz (∼18.5 days; Hicken et al 2007) or typical SNe Ia (∼19 days; e.g., Conley et al 2006). Assuming t r = 20 days for SN 2009dc, we derive the 56 Ni mass of 1.2 ± 0.3 M for the no host extinction case.…”
Section: Bolometric Light Curve and 56 Ni Massmentioning
confidence: 78%
“…The slow evolution of brightness in SN 2009dc around the maximum suggests that the rising time of the bolometric luminosity is comparable to or slightly longer than those of SN 2006gz (∼18.5 days; Hicken et al 2007) or typical SNe Ia (∼19 days; e.g., Conley et al 2006). Assuming t r = 20 days for SN 2009dc, we derive the 56 Ni mass of 1.2 ± 0.3 M for the no host extinction case.…”
Section: Bolometric Light Curve and 56 Ni Massmentioning
confidence: 78%
“…The light curves evolve very slowly. For SN 2009dc, Silverman et al (2011 reported a first detection on an image taken 21 d before B-band maximum, and estimated a rise time of 23 ± 2 d, significantly longer than in normal SNe Ia (17-20 d; Conley et al 2006;Hayden et al 2010). Also the decline rates after peak are among the slowest ever observed for SNe Ia, with ∆ m 15 (B) between 0.7 and 0.9.…”
Section: Early-time Light Curves and Peak Luminositymentioning
confidence: 98%
“…As discussed in § 4.2, we have assumed for SN 2005hk that the explosion occurred 15 days before B maximum. For SN 2001el and SN 1999by, we have taken this number to be 18.1 and 11.0 days before B maximum, respectively, which we derived from the average B light-curve rise time given by Conley et al (2006) after application of stretch values appropriate for both SNe. Figure 15 emphasizes the subluminous nature of SN 2005hk, but also shows that these events are not as extreme as the SN 1991bg-like SNe Ia.…”
Section: Absolute Magnitudes and Uvoir Bolometric Light Curvementioning
confidence: 99%